2004
DOI: 10.1099/ijs.0.63190-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of artisanal Italian cheeses reveals Enterococcus italicus sp. nov.

Abstract: The taxonomic positions of seven atypical Enterococcus strains, isolated from artisanal Italian cheeses, were investigated in a polyphasic study. By using 16S rRNA gene sequencing, DNA-DNA hybridization and intergenic transcribed spacer analysis, as well as by examining the phenotypic properties, the novel isolates were shown to constitute a novel enterococcal species. Their closest relatives are Enterococcus sulfureus and Enterococcus saccharolyticus, having a 16S rRNA gene sequence similarity of 96?7 %. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 34 publications
1
37
0
2
Order By: Relevance
“…T and E. italicus LMG 22039 T were highly related, having about 100% 16S rRNA gene sequence similarity and an analogous atpA sequence similarity, which suggests that E. saccharominimus and E. italicus might be synonymous species (10,39 T constituted distinct branches. E. solitarius is phylogenetically more closely related to Tetragenococcus than to the other enterococci (11,20).…”
Section: Resultsmentioning
confidence: 94%
“…T and E. italicus LMG 22039 T were highly related, having about 100% 16S rRNA gene sequence similarity and an analogous atpA sequence similarity, which suggests that E. saccharominimus and E. italicus might be synonymous species (10,39 T constituted distinct branches. E. solitarius is phylogenetically more closely related to Tetragenococcus than to the other enterococci (11,20).…”
Section: Resultsmentioning
confidence: 94%
“…T and E. saccharolyticus ATCC 43076 T (Fortina et al, 2004 T (97.0 %) (Fortina et al, 2004). Lower sequence similarities (,97 %) were found to other described species of the genus Enterococcus (Fig.…”
mentioning
confidence: 90%
“…T and E. saccharolyticus ATCC 43076 T (Fortina et al, 2004). The DNA G+C content of the strain was 37.8 mol%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the results of 16S rRNA gene sequencing, SDS-PAGE analysis of WCP profiles, and DNA-DNA reassociation experiments indicated that strain ATCC BAA-780 (CDC PNS-E1) corresponds to Enterococcus italicus, a new species that was proposed to designate a group of isolates recovered from artisanal Italian cheese (4). Comparative analysis of the 16S rRNA gene sequence of our isolate ATCC BAA-780 also showed species-level similarity with the sequence of Enterococcus saccharominimus, confirming the recent finding reported by Naser et al (7) that E. italicus and E. saccharominimus (also represented by isolates obtained from dairy products) are a single species.…”
mentioning
confidence: 99%